Out of their comfort zone : student reactions to cultural challenges while travel writing - Duffy, Andrew (2019)
Many journalism students harbour desires of becoming travel writers. And yet, when taken on a travel-writing trip, how do they react when confronted with the reality? And how does their own social framework influence their perception of a foreign country? This article uses content analysis of travel articles written by mainly Singaporean journalism students on two travel-writing practicums in Southeast Asia, to examine choice of topic: the role of the travel writer as commentator and intermediary and the representation of the ‘other’ country for consumption by a ‘home’ audience. Its impact on journalism education is to encourage students to consider their own reaction to and creation of the Other—more commonly done in international reporting, or covering topics such as immigration, homosexuality, disability, race and religion—and it is hoped that insights from this research can be applied to education in other forms of journalism. Finally, it considers whether student journalists from an Asian city state that emerged from the shadow of empire can escape recreating the patterns of colonialism implicit in much Western travel writing.